2018
DOI: 10.1037/xlm0000459
|View full text |Cite
|
Sign up to set email alerts
|

Generating lies produces lower memory predictions and higher memory performance than telling the truth: Evidence for a metacognitive illusion.

Abstract: Manipulations that induce disfluency during encoding generally produce lower memory predictions for the disfluent condition than for the fluent condition. Similar to other manipulations of disfluency, generating lies takes longer and requires more mental effort than does telling the truth; hence, a manipulation of lie generation might produce patterns similar to other types of fluency for memory predictions. The current study systematically investigates the effect of a lie-generation manipulation on both actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 93 publications
1
22
0
Order By: Relevance
“…Recent research has established that people's beliefs about the impact of a cue can influence their JOLs (e.g., Hu et al, 2015;Jia et al, 2016;Mueller & Dunlosky, 2017;Mueller, Dunlosky, & Tauber, 2016;Mueller, Dunlosky, Tauber, & Rhodes, 2014;Mueller, Tauber, & Dunlosky, 2013;Susser, Jin, & Mulligan, 2016;Undorf & Zimdahl, 2019;Witherby & Tauber, 2017). One way that this contribution of memory beliefs has been evaluated is with questionnaires probing for people's beliefs about their memory (Besken, 2016;Jia et al, 2016;Koriat, Bjork, Sheffer, & Bar, 2004;Kornell, Rhodes, Castel, & Tauber, 2011;Li et al, 2017;Mueller et al, 2016;Mueller, Dunlosky, Tauber, & Rhodes, 2014;Mueller et al, 2013;Price, McElroy, & Martin, 2016;Witherby & Tauber, 2017, 2018.…”
Section: Contribution Of Beliefs To Judgments Of Learningmentioning
confidence: 99%
“…Recent research has established that people's beliefs about the impact of a cue can influence their JOLs (e.g., Hu et al, 2015;Jia et al, 2016;Mueller & Dunlosky, 2017;Mueller, Dunlosky, & Tauber, 2016;Mueller, Dunlosky, Tauber, & Rhodes, 2014;Mueller, Tauber, & Dunlosky, 2013;Susser, Jin, & Mulligan, 2016;Undorf & Zimdahl, 2019;Witherby & Tauber, 2017). One way that this contribution of memory beliefs has been evaluated is with questionnaires probing for people's beliefs about their memory (Besken, 2016;Jia et al, 2016;Koriat, Bjork, Sheffer, & Bar, 2004;Kornell, Rhodes, Castel, & Tauber, 2011;Li et al, 2017;Mueller et al, 2016;Mueller, Dunlosky, Tauber, & Rhodes, 2014;Mueller et al, 2013;Price, McElroy, & Martin, 2016;Witherby & Tauber, 2017, 2018.…”
Section: Contribution Of Beliefs To Judgments Of Learningmentioning
confidence: 99%
“…The experiment closest to the current study in design, Gerlach et al ( 2014) Experiment 1, used 24 adults per group. Other studies that investigate JOLs for processing fluency (e.g., Besken, 2018;Mueller et al, 2013) or emotions (e.g., Hourihan & Bursey, 2017) usually use sample sizes ranging from 20 to 40 per group. A statistical power analysis through G-power (Faul et al, 2009) revealed that a sample size of 30 was necessary to detect a middle-sized effect of f = .25 with a power of .90, at an alpha of .05.…”
Section: Participantsmentioning
confidence: 99%
“…In addition to memory, the present study also investigates the effects of imagination of past and future hypothetical events on metamemory, which refers to people's beliefs and predictions about how their memory operates. Although there are studies showing that people can accurately predict their subsequent memory performance (Nelson & Dunlosky, 1991), other studies show that under certain circumstances there might be mismatches between people's memory predictions and actual memory performance (Benjamin et al, 1998;Besken, 2016Besken, , 2018Besken & Mulligan, 2013;Yue et al, 2013). Emotional valence is one factor that sometimes causes a mismatch between predicted and actual memory performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Besken (2018) examined the relationship between deception and memory while also assessing the metamemory of liars and truth-tellers. Participants provided correct (truthful) or incorrect (deceptive) answers to a series of general knowledge questions, and subsequently rated their confidence that they would remember their response on a later memory test (a "judgment of learning").…”
Section: Volitional Deception and Memorymentioning
confidence: 99%